The Candy Bombers : the Untold Story of the Berlin Aircraft and America's Finest Hour - Cherny, Andrei (New York : Penguin Group US, 2008)
The Candy Bombers.
Keywords: 1945-1953; United States; Diplomatic relations; Berlin (Germany) -- History -- Blockade, 1948-1949.; Electronic books; History